Analisis Konflik Perebutan Wilayah Pembangunan Eco-City di Rempang, Kepulauan Riau Melalui Teori Johan Galtung - Ramadani, Nuri Salsa Bella; Rahmawati, Sherly Widya; Subandi, Yeyen (SENTRI: Jurnal Riset Ilmiah, 2025)
This study examines the territorial conflict surrounding the Rempang Eco City development project in the Riau Islands, designated as a National Strategic Project (PSN) valued at IDR 381 trillion. The conflict emerged from the clash between large-scale investment-driven development interests and the traditional land rights of the 16 Malay Indigenous Villages that have inhabited the area for generations. The lack of communication and transparency from both central and regional governments regarding relocation plans triggered mass protests and violent clashes in September 2023. This research employs a qualitative method based on John W. Creswell’s framework, utilizing case study and phenomenological approaches. Data were collected from credible sources, including official reports, government documents, and reputable online media. The analysis applies Johan Galtung’s theory, particularly the Triangle of Violence, to identify and interpret the forms of conflict and violence that occur. The results show that the conflict reflects both structural and direct violence, where structural violence appears in relocation policies that disregard the legal recognition of indigenous land rights, while direct violence is evident in the repressive actions of security forces against protesting residents. The findings further indicate that despite the government’s humanistic approach in preparing relocation sites and facilities, community resistance remains strong due to unresolved issues of justice, identity, and cultural preservation. Overall, these findings emphasize the urgent need for participatory and equitable conflict resolution frameworks in implementing sustainable development projects across Indonesia.